THE USE OF INFORMATION COMMUNICATION AND TECHNOLOGY IN ENGLISH LANGUAGE TEACHING - Febria Zananda, Tiray (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2020)
A new model of technology used to improve teaching and studying literacy to arrange the class is just one way to improve the teaching and learning process. Teachers can come up with different models in their teaching processes based on the prior observation, research and invesigation, related to cultural awareness and scientific designs through technology. The teachers should provide some evidences and implications for the arrangement of classes and more efforts need to be made in order to get a full understanding of relations network technology establishment in the interactive class especially in English Language Teaching (ELT).